Risk Analysis of Work Accidents in The Building Revitalization Project “Y” City Semarang by PT. X with Fault Tree Analysis (FTA) Method - Rizqia, Nadya Nur; Hapsari, Dessy Yasnia; Ariyanto, Talitha Irmadella Radhwa; Firmansyah, Hanif Tria; Alhasfi, Doni; Fong, Michelle Seow Seak (Universitas Negeri Semarang, 2025)
The construction industry is hazardous due to its tendency to cause accidents. In constructing a multi-storey building, one of the risks that has the potential for work accidents is the risk of falling from a height. This research was conducted on the “Y” building revitalization project in Semarang city. This study aims to analyze the factors that are the basic causes of unwanted events in the project's revitalization using the Fault Tree Analysis (FTA) method. This research is descriptive observational research with analysis based on field observations and supported by literature studies from previous research. The results showed two of the most dangerous risks, namely